Finite Element Modelling of Welding Residual Stress and Its Influence on Creep Behavior of a 2.25Cr-1Mo-0.25V Steel Cylinder. (2015) - Zhou, Y.; Chen, X.D.; Fan, Z.C.; Rao, S.X.
Abstract: Thermo-mechanical finite element analysis was performed to predict the residual stress distribution in a single-U butt weld of a 2.25Cr-1Mo-0.25 V steel cylinder using ANSYS. An axisymmetric model of the cylinder with a wall thickness of 150 mm, having a 55-pass weld, was adopted in the study to reduce computation complexity. The influence of welding residual stress on creep behavior of the welded joint subjected to internal pressure under operation condition was investigated using the continuum damage mechanics (CDM) theory. The results showed that the distribution of welding residual stress in the multi-pass weld was quite complex, and the residual stress can be relaxed to a lower level in a short time during creep, which can accelerate the creep damage of the welded joint.